2006
DOI: 10.1093/ei/cbl005
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Stated Preferences for Cholera and Typhoid Vaccines With Time to Think in Hue, Vietnam

Abstract: We examine the effect of giving respondents time to think about their stated choices (SC) in a survey of cholera and typhoid vaccine preferences in Hue, Vietnam. Because neither vaccine is widely available in Vietnam, we used the SC approach (a stated preference technique) and gave half of our respondents overnight to think about their choices to make the hypothetical valuation scenario as similar to a real-life choice situation as possible. Respondents who were given extra time made fewer choices that violate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 15 publications
3
30
1
Order By: Relevance
“…This would involve letting respondents temporarily close the survey right after the valuation question or choice tasks and contacting them again the next day to collect their responses. The relevant literature has shown that this procedure leads to fewer preference errors and higher choice certainty (Whittington et al 1992;Cook et al 2007Cook et al , 2012. The results of the present study also show where increased response time leads to less error variance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This would involve letting respondents temporarily close the survey right after the valuation question or choice tasks and contacting them again the next day to collect their responses. The relevant literature has shown that this procedure leads to fewer preference errors and higher choice certainty (Whittington et al 1992;Cook et al 2007Cook et al , 2012. The results of the present study also show where increased response time leads to less error variance.…”
Section: Discussionsupporting
confidence: 77%
“…Whittington et al 1992;Cook et al 2007Cook et al , 2012Svedsäter 2007). In such surveys, respondents are interviewed face-to-face in their homes, given a certain time to think about the valuation scenario and their responses (typically one night) and contacted again on the second day to state their WTP or discrete choices.…”
Section: Response Time Modelsmentioning
confidence: 99%
“…However, studies have shown that experimental situations involving real payoffs can also lead to biased estimates (e.g., Alpízar et al 2008;List et al 2004). 2 There are other suggestions for how to reduce hypothetical bias, for example, ex-post calibration of the WTP responses with follow-up questions on certainty (e.g., Champ et al 1997;Champ and Bishop 2001) and time-tothink protocols (Cook et al 2007;Whittington et al 1992). …”
Section: Introductionmentioning
confidence: 99%
“…Surveys can then be collected, or sent back by mail. In the study by Cook et al (2007), respondents made fewer inconsistent responses in a treatment where they were given time to think compared to a standard treatment, and the WTP was also significantly lower. There are a number of features of this design that can reduce hypothetical bias, and several of them have to do with contextual differences between the survey situation and the corresponding actual situation.…”
Section: Hypothetical Biasmentioning
confidence: 90%
“…This is nothing new for survey practitioners, and for example the suggestion to remind subjects about the budget constraint is one way to try to widen the focus of the respondents. Another interesting way of addressing this, which has great potential, is the time-to-think protocol (Whittington et al, 1992;Cook et al, 2007). The idea is very simple, and it can be done in several different ways.…”
Section: Hypothetical Biasmentioning
confidence: 99%